Blogi internetowe polityków a identyfikacje partyjne - Wichura, Jarosław (Political Preferences, 2013)
For po1itics, just 1ike any member of the pub1ic, the Internet is a very convenient medium. It not on1y a11ows for a re1ative1y 1ow cost to reach diverse customers, but it is a1so an exce11ent too1 for meeting the requirements of the po1itics persona1ization. Not on1y their own websites, on-1ine discussions and e-mai1 offer today a po1itician possibi1ity of mediating communication with citizens (voters). Becoming increasing1y popu1ar, b1og offers many exciting opportunities to provide information. Every po1itica1 party can find a po1itician who owns and runs a b1og (inc1uding Joanna Senyszyn, Wa1demar Paw1ak, Ryszard Czarnecki, Janusz Korwin-Mikke, Marek Miga1ski). Most of them treats virtua1 notebooks as a too1 to present their views and image. They emphasize certain information which they be1ieve and have not been adequate1y provided by other media. Undoubted1y, on1ine diaries begin to p1ay an increasing1y important ro1e today in po1itica1 communication. Even though they are much more "poor" from par1iamentary websites, because they contain on1y the texts pub1ished by the author, they are a great advantage of persona1istic character. Popu1arity of b1ogs among po1iticians (not on1y in Po1and) is steadi1y increasing. One of the things attesting to the va1idity of this court is its constant evo1ution. On1ine diaries are more and more powerfu1. You can now post on b1og not on1y a text, but a1so a photo, short video or audio fi1e. It shou1d be noted that the po1itica1 debate is c1ose1y dependent on the media and chan- ging with the emergence of new communication too1s. B1ogs made a significant transfers in this area. For the purposes of this artic1e, subject of study focused on two 1eve1s of ana1ysis, for the e1ections to the Par1iament (if they were he1d this Sunday) and in the context of po1itica1 ideo1ogy. The ana1ysis of empirica1 data was re1atedto the two main issues: ownership and operation of po1itica1 b1ogs and track their entries by the voters.